Makna Pendampingan Doula Bagi Ibu Hamil, Sebuah Tinjauan Psikologis - Eva Nur Rachmah; Suryanto (Fakultas of Psychology, Universitas Muria Kudus, 2025)
Childbirth support is a crucial aspect in maintaining the physical and psychological well-being of pregnant women. One form of support that is becoming increasingly recognized is the presence of a Doula, a non-medical companion who provides emotional, informational, and physical support throughout pregnancy and delivery. This study aims to examine the meaning of Doula support for pregnant women from a psychological perspective. The method used was a qualitative approach with a phenomenological design. The selection of informants in this study focused on pregnant women who had actually experienced or were directly involved in the phenomenon of Doula support, with purposive selection based on their relevance and experience. The review results indicate that the presence of a Doula can minimize anxiety, increase self-confidence, and help pregnant women feel calmer and more empowered in facing the labor process. Furthermore, Doula support contributes to strengthening the emotional bond between mother and fetus, and fosters a more positive birth experience. From a psychological perspective, Doula support is meaningful as a form of support system that provides a sense of security, connectedness, and mental empowerment for pregnant women. Thus, Doula support has been shown to facilitate more adaptive coping strategies and strengthen mothers' self-confidence in undergoing childbirth and emphasizes the importance of considering the presence of Doulas as part of maternal services, both through public education and the integration of non-medical support into the health care system, to improve the quality of the childbirth experience while preventing maternal psychological problems. Pendampingan persalinan merupakan aspek penting dalam menjaga kesejahteraan fisik dan psikologis ibu hamil. Salah satu bentuk dukungan yang mulai banyak dikenal adalah kehadiran Doula, yaitu pendamping non-medis yang memberikan dukungan emosional, informasional, dan fisik selama masa kehamilan hingga persalinan. Penelitian ini bertujuan untuk meninjau makna pendampingan Doula bagi ibu hamil dari perspektif psikologis. Metode yang digunakan adalah menggunakan pendekatan kualitatif dengan desain fenomenologi. Penentuan informan dalam penelitian ini berfokus pada ibu hamil yang benar-benar mengalami atau terlibat langsung dalam fenomena pendampingan Doula, dengan pemilihan secara purposive sesuai relevansi dan pengalamannya. Hasil review menunjukkan bahwa kehadiran Doula dapat meminimalisir kecemasan, meningkatkan rasa percaya diri, serta membantu ibu hamil merasa lebih tenang dan berdaya dalam menghadapi proses persalinan. Selain itu, dukungan Doula berkontribusi dalam memperkuat ikatan emosional antara ibu dan janin, serta menumbuhkan pengalaman persalinan yang lebih positif. Dari perspektif psikologis, pendampingan Doula bermakna sebagai bentuk support system yang memberi rasa aman, keterhubungan, dan penguatan mental bagi ibu hamil. Dengan demikian, dukungan Doula terbukti memfasilitasi strategi coping yang lebih adaptif serta memperkuat keyakinan diri ibu dalam menjalani persalinan serta menekankan pentingnya mempertimbangkan kehadiran Doula sebagai bagian dari layanan maternal, baik melalui edukasi publik maupun integrasi pendampingan non-medis dalam sistem pelayanan kesehatan, guna meningkatkan kualitas pengalaman persalinan sekaligus mencegah masalah psikologis maternal.